Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Kelompok Tani - Vita Nur Tianing; Siswahyudianto (Idarotuna : Journal of Administrative Science, 2022)
Consumer goals are one of the main things in a business. Because by making efforts that can be done, namely continuing to maintain and increase satisfaction with consumers, consumers will more often repurchase an item or service that has been consumed or used. Consumer goals are determined by several things, including price, product quality, and service quality. This study analyzed the effect of price, product quality, and service quality on consumer satisfaction at the "Belimbing Artha Mandiri" Farmer Group, Bono Village, Boyolangu District, Tulungagung Regency. This study uses a quantitative approach using a survey research type through a questionnaire. The population in this study were consumers in the Artha Mandiri Belimbing Farmer Group in the Boyolangu District. The sample in this study was 40 respondents. The results of the study conclude that: Price has a positive effect on consumer satisfaction of the Artha Mandiri Belimbing Farmers Group, product quality has a positive effect on consumer satisfaction of the Artha Mandiri Belimbing Farmers Group, and Service quality has a positive effect on consumer satisfaction of the Artha Mandiri Belimbing Farmers Group ", and Price, product quality, and the quality of service has a simultaneous and positive effect on consumer satisfaction of the "Belimbing Artha Mandiri" Farmer Group. Almost all consumer goals are clarified by the variables of price, product quality, and service quality. Then to be further explained by other variables or not included in this research model.